2014
DOI: 10.1007/s00414-014-1033-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric sex estimation from 3D computed tomography os coxae model and its validation in skeletal remains

Abstract: In the last decade, the advances in imaging technologies have intensified the use of multislice computed tomography (MSCT) for anthropological purposes. The published literature has proved it to be a suitable tool for establishing sexually dimorphic characteristics in different anatomical areas. In this context, the main purpose of the present study was to explore the accuracy of traditional morphometric method when applied to data acquired in three-dimensional (3D) reconstructed os coxae of living Spanish pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 34 publications
6
17
0
Order By: Relevance
“…It also agrees with Djorojevic et al, 2014, who concluded the presence of greatest differences between both sexes in innominate height (IHM) as it reflects the overall size of the body and it is it is generally higher in men [4].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It also agrees with Djorojevic et al, 2014, who concluded the presence of greatest differences between both sexes in innominate height (IHM) as it reflects the overall size of the body and it is it is generally higher in men [4].…”
Section: Resultssupporting
confidence: 90%
“…There are not general diagnostic criteria that can be transferred from one population to another. Forensic anthropologists are attempting to develop population-specific objective standards that can be used in identification of human skeletal remains [4,9]. whites and blacks, they concluded that the accuracy of sciatic notch range from 73% to 77%, and attributed that it is quite difficult to quantify the differences in greater sciatic notch size, angle, and shape [11].…”
Section: Discussionmentioning
confidence: 99%
“…The highly accurate reliability of the pelvis to provide information about the sex of adult individuals has been widely recognized [e.g., [1][2][3]. Nevertheless, being often unavailable or insufficiently preserved to yield relevant set of data for assessing the sex, there is an imperative need to accomplish the positive identification from other skeletal elements, preferable long bones [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the recovered victims had viscera displaced into the thoracic cavity resulting in the accidental discovery of an [18][19][20][21][22] week fetus in the chest radiograph of a young female. In addition several sex estimation methods have been developed by means of Radiography [25][26] and Computed Tomography [27][28].…”
Section: Introductionmentioning
confidence: 99%